Backtrajectory reconstruction of water vapour and ozone in-situ observations in the TTL - F. Ploeger; P. Konopka; R. Müller; G. Günther; J.-U. Grooss; C. Schiller; F. Ravegnani; A. Ulanovski; M. Riese (Meteorologische Zeitschrift, 2012)
Water vapour and ozone in-situ observations in the tropical tropopause layer (TTL) during the three tropical campaigns SCOUT-O3, AMMA and TroCCiNOx are reconstructed from diabatic and kinematic backtrajectories, with the reconstruction method for the tracer fields based on freeze-drying and photochemichal ozone production. The results using diabatic trajectories show that both water vapour and ozone in-situ observations can be well reconstructed from trajectories. Consequentially, in-situ observations agree with the assumption of freeze-drying due to the large-scale temperature field as the main control mechanism for water vapour and photochemical production and transport as main control mechanisms for tropical ozone. The kinematic ozone reconstruction, however, shows a large high-bias during SCOUT-O3 and a too strong variability during all campaigns, due to excessive transport of stratospheric ozone into the TTL. We conclude that kinematic reconstructions of in-situ observations are less reliable than diabatic, due to unrealistic inhomogeneities in the velocity field.